Działalność społeczno-polityczna Ligi Kobiet w województwie lubelskim w latach 1945–1957 - Maleszak, Sylwia (Komunizm: System - Ludzie - Dokumentacja, 2023)
The Social and Civic Women’s League was established in 1945. Its scope of activities was very wide: the organization participated in activities not only in favor of women in large urban and industrial centers of Lublin Voivodeship, but also in small towns or villages. Intended to become a more popular organization, the League was constantly acquiring new members. In the first years after the Second World War, the Women’s League was mainly occupied with charitable activities. It supported the poor and the elderly by creating nursery homes and dining halls. In Lublin Voivodeship, members of the organization conducted training for women. The activists participated in efforts to counteract illiteracy or social pathologies. They conducted lectures and courses devoted to household management. Year 1948 brought ideological and propagandist changes in the organization. The period of Stalinization forced the organization to shift from social to political activities. The association was subordinated to the contemporary authorities. The central mechanism of making and forcing decisions had a negative impact on the bottom-up activities of women and limited their natural social activity. It is hard to assess conclusively the actions of the Women’s League. However, many initiatives undertaken by the League were met with the approval of the inhabitants of the Lublin region. Those initiatives also improved the life of women and increased their chances for labor market entry